Training Advertising Video for Multimedia Teachers in Improving the Quality of Skills Competency Tests - Maya Purnama Sari; Nala Nandana Undiana; Fenny Puspitasari; Dian Rinjani; Nurhidayatulloh Nurhidayatulloh; Agus Juhana; Dzulya Istiqomah (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2023)
This community service program applied a training method to improve teacher skills as the primary source of learning for students in schools in order to cultivate high-quality of high vocational school students so that they can be absorbed by the business and industrial sectors. The training was carried out within a period of three months covering various topics from basic understanding of videography, utilizing video advertisement ideas, video processing techniques and audio processing techniques. The objective of this training was to equip qualified teachers with the ability to foster high-quality vocational students who possess the skills desired by the business and industrial sectors. The training successfully resulted in six teachers who were able to independently create advertising videos, while the other four teachers still required rfurther training to become more accustomed to video production. As a follow-up to this activity, an electronic book accompanied by a video advertisement production tutorial will be developed to support the professional development needs of the participating teachers at SMKN 14 Bandung.